Comparison of PCR, Isoenzyme Analysis, and Antigen Detection for Diagnosis of Entamoeba histolytica Infection - Haque, Rashidul (American Society for Microbiology, 1998)
The diagnosis of amebiasis by microscopic identification of the parasite in stool is insensitive and unable to distinguish the invasive parasite Entamoeba histolytica from the commensal parasite E. dispar. In this study, we have tested a PCR technique for the detection of E. histolytica and compared it with isoenzyme analysis and the TechLab E. histolytica-specific antigen detection test. The nested-PCR test we used is based on amplification of the small subunit rRNA gene of E. histolytica and E. dispar followed by restriction digest analysis of the PCR product. Single stool samples were obtained from 98 patients from Dhaka, Bangladesh, with diarrhea: 88 patients diagnosed by microscopy and/or culture with E. histolytica and/or E. dispar infection and 10 patients without infection. Isoenzyme analysis identified 53 of the infections as E. histolytica and 28 as E. dispar. PCR and isoenzyme identification of E. histolytica agreed in 96% (51 of 53) of amebic cultures. PCR for E. histolytica was negative in all 10 samples that were negative for E. histolytica by isoenzyme and antigen detection. PCR and antigen detection had comparable sensitivities when performed directly on fresh stool specimens, identifying 87% (46 of 53) and 85% (45 of 53), respectively, of E. histolytica infections identified by isoenzyme analysis. The correlation of results by antigen detection and PCR for identification of E. histolytica in stool was 93% (45 of 48 cases). Mixed infections with E. histolytica and E. dispar were detected by PCR in 14% (12 of 88) of cases. In conclusion, all three techniques for specific identification of E. histolytica in fresh stool showed excellent correlation. Only the TechLab E. histolytica antigen detection test was both rapid and technically simple.